Facilitated transporters mediate net efflux of amino acids to the fetus across the basal membrane of the placental syncytiotrophoblast. - Cleal, J; Glazier, J; Ntani, G; Crozier, SR; Day, P; Harvey, N; Robinson, S; Cooper, C; Godfrey, K; Hanson, M; Lewis, R (2011)
Fetal growth depends on placental transfer of amino acids from maternal to fetal blood. The mechanisms of net amino acid efflux across the basal membrane (BM) of the placental syncytiotrophoblast to the fetus, although vital for amino acid transport, are poorly understood. We examined the hypothesis that facilitated diffusion by the amino acid transporters TAT1, LAT3 and LAT4 plays an important role in this process, with possible effects on fetal growth. Amino acid transfer was measured in isolated perfused human placental cotyledons (n = 5 per experiment) using techniques which distinguish between different transport processes. Placental TAT1, LAT3 and LAT4 proteins were measured, and mRNA expression levels (measured using real-time quantitative-PCR) were related to fetal and neonatal anthropometry and dual-energy X-ray absorptiometry measurements of neonatal lean mass in 102 Southampton Women's Survey (SWS) infants. Under conditions preventing transport by amino acid exchangers, all amino acids appearing in the fetal circulation were substrates of TAT1, LAT3 or LAT4. Western blots demonstrated the presence of TAT1, LAT3 and LAT4 in placental BM preparations. Placental TAT1 and LAT3 mRNA expression were positively associated with measures of fetal growth in SWS infants (P < 0.05). We provide evidence that the efflux transporters TAT1, LAT3 and LAT4 are present in the human placental BM, and may play an important role in the net efflux of amino acids to the fetus. Unlike other transporters they can increase fetal amino acid concentrations. Consistent with a role in placental amino acid transfer capacity and fetal growth TAT1 and LAT3 mRNA expression showed positive associations with infant size at birth.